Association between iron tablet utilization and anemia status in pregnant women at Woyla Timur Community Health Center - Ita Susanti Ita; Asmima Yanti; Nur Afriza (International Journal of Nursing and Midwifery Research, 2026)
Anemia in pregnant women remains a health problem that can increase the risk of complications for the mother and fetus. One effort to prevent anemia during pregnancy is through regular consumption of iron tablets. However, the level of compliance of pregnant women in consuming iron tablets remains a challenge in maternal health programs. This study is a quantitative analytical study with a cross-sectional approach, which was conducted in the Working Area of the Woyla Timur Community Health Center, West Aceh Regency in January 2026. The study population was all 50 pregnant women in the third trimester. The sampling technique used total sampling so that the entire population was used as a research sample. Data were analyzed using the Chi-square test to examine the association between iron tablet utilization and anemia status among pregnant women receiving antenatal care at the Woyla Timur Community Health Center. The study findings demonstrated a statistically significant association between iron tablet utilization and anemia status among pregnant women receiving antenatal care at the Woyla Timur Community Health Center. The results of the Chi-Square test analysis obtained a p-value = 0.000 (p <0.05). A statistically significant association was observed between iron tablet utilization and anemia status among pregnant women at the Woyla Timur Community Health Center. Based on these findings, interventions focused on education, counseling, and regular monitoring should be enhanced to support optimal iron tablet utilization during pregnancy.